Level of Environmental Friendliness of Collapsible Trap Based in the Archipelagic Fishing Port of Karangantu Serang City Banten Province - Yeni Marliana; Adi Susanto (Jurnal Perikanan dan Kelautan, 2015)
The archipelagic fishing port of Karangantu is a main place of swimming crab fishing and processing in Serang City. The fisherman using collapsible trap to catch swimming crab in this port. The objective of this research is to analyze the environmental friendliness level of collapsible trap was used by fishermen. The research was carried out by experimental fishing method on 20th January –17th February 2015 using a collapsible trap that has a length x width x height: 41 cm x 29 cm x 18 cm. This research used four criteria for assessing the environmental friendliness is a high selectivity, low by-catch, high quality of catches and low impact to biodiversity. The catches consist of Portunus pelagicus (82%), Nibea albiflora (5%), Harpiosquilla raphidea (3%), Octopus sp. (3%), Epinephelus sp. (2%), Terapon jarbua (1.5%), Podopthalmus vigil (2%), and Charibydis feriatus (1.5%). The proportion of main catch of 86%, 97% of live catch, and diversity index of 0.84. The total scores is 20, its mean a collapsible trap is environmentally friendly of fishing gear to catch swimming crab.